2003
DOI: 10.1292/jvms.65.287
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Bovine Immunodeficiency Virus and Bovine Leukemia Virus in Dairy and Beef Cattle in Hokkaido.

Abstract: ABSTRACT. Serological survey of bovine immunodeficiency virus (BIV) and bovine leukemia virus (BLV) infection was conducted in dairy cattle from 10 different regions of Hokkaido, Japan. Among 390 cattle, 11.0% of cattle were BIV-seropositive and 3.3% were BLV-seropositive. Moreover, in two dairy farms, where bovine leukosis has been reported, prevalence of BIV infections were 6.4 and 9.1%, respectively. In contrast, among 150 beef cattle, 16.6% were BIV-seropositive while none was BLV-seropositive. Dual infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
1
8
0
1
Order By: Relevance
“…Although BIV infected cattle have been identified in some countries neighboring Iran [4,19], to the best of our knowledge this is the first report of BIV infection in Iranian Holstein cattle. Although we studied only a small number of animals, the prevalence we found of 20.3% is similar to that reported from other Asian countries (12% in Turkey [19] to 35% in Korea [20]), and neighboring countries such as Pakistan (16 %) [4,13]. The prevalence of BLV infection (17%) in the current study was also similar to that of other Asian and non Asian countries (9 to 33 %) [21][22][23][24].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Although BIV infected cattle have been identified in some countries neighboring Iran [4,19], to the best of our knowledge this is the first report of BIV infection in Iranian Holstein cattle. Although we studied only a small number of animals, the prevalence we found of 20.3% is similar to that reported from other Asian countries (12% in Turkey [19] to 35% in Korea [20]), and neighboring countries such as Pakistan (16 %) [4,13]. The prevalence of BLV infection (17%) in the current study was also similar to that of other Asian and non Asian countries (9 to 33 %) [21][22][23][24].…”
Section: Discussionsupporting
confidence: 86%
“…Following experimental infections, cattle may have transient increases in lymphocytes, lymphoid hyperplasia, atypical lymphosarcoma, and secondary bacterial infections [6,10,11]. It has also been suspected that the stress of parturition in BIV infected cows is associated with the progression of bovine leukemia virus (BLV) infections [8,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The cow was fertilized naturally, and the calf was placed in conventional housing with the dam, and monitored for the presence of BLV-specific antibodies, as previously described [24,26,27]. Whole blood samples and sera were collected at 3-week intervals.…”
Section: Methodsmentioning
confidence: 99%
“…With the exception of a few European countries, EBL is considered to have a worldwide distribution. Although the majority of infected cattle remain clinically asymptomatic, invisible losses in productivity have a significant economic impact on the dairy industry [4,24,26]. BLV is an oncogenic retrovirus of the Retroviridae family.…”
Section: Introductionmentioning
confidence: 99%
“…Meas and collaborators reported that env gene sequences from circulating viruses in Japan (Usui, Meas, Konnai, Ohashi, & Onuma, ), Pakistan (Meas, Seto, et al, ) and Cambodia (Meas, Ohashi, et al, ) were shorter and presented more substitutions compared to isolates from the USA (R29, Florida 112 and Oklahoma 40). These regions remain unknown for circulating viruses in Mexico.…”
Section: Resultsmentioning
confidence: 99%